DID-Matching Methodology Applied to Export Promotion Public Policy - Geldres W., Valeska V.; Etchebarne L., M. Soledad; Bustos M., Luis H. (Estudios de Administración, 2009)
This article shows how the Did Matching Methodology as an impact evaluation tool can be applied to a specific exportation public policyinstrument, called Export Marketing Assistance (EMA). The article presents a study in which 59 export firms of the Araucanía region in Chile were analyzed. The results show a positive relationship between export performance and exportation public policy instrument used. However, this relationship is not statistically significant.